Early Orthodontic Treatment in Children: A Qualitative Exploration of Orthodontists’ Perspectives and Practices in Saudi Arabia - Guna Shekhar Madiraju; Yousef Majed Almugla (Healthcare, 2026)
Background and Objectives: The optimal timing of orthodontic intervention in children remains debated, particularly during the mixed dentition phase. Despite potential benefits, variability in clinical decision-making persists. This study explored orthodontists’ perceptions, clinical practices, and clinical decision-making regarding the timing of early orthodontic intervention in Saudi Arabia. Materials and Methods: An interpretive qualitative study was conducted using semi-structured interviews with nineteen licensed orthodontists practicing in Saudi Arabia. Participants were purposively sampled to ensure diversity in clinical experiences and practice settings. Interviews were conducted in English and Arabic, using detailed contemporaneous field notes that were subsequently expanded for analysis. Data were analyzed using thematic analysis following Braun and Clarke’s framework, with iterative coding supported by investigator triangulation, reflexive memoing, and participant validation. Data collection continued until thematic saturation was achieved. Results: Four major themes were identified. Early intervention was widely perceived as beneficial, particularly for functional problems, Class III malocclusions, and crossbites. However, decision-making was highly individualized, with many clinicians adopting a selective approach and deferring treatment in mild cases. Variation in clinical reasoning was observed across individual participant accounts, reflecting clinical judgment and contextual influences. Key barriers included limited parental awareness, financial constraints, and delayed referrals. System-level factors, such as variability in insurance coverage, referral pathways, and the lack of structured early screening programs, were identified as important influences on access to timely care. Conclusions: Early orthodontic intervention should be applied selectively, based on clinical indications and patient-specific factors. The context-specific findings highlight the need for appropriately tailored guidance, improved referral systems, structured early screening, and consideration of clinical, practitioner-related, and healthcare system factors to support consistent, patient-centered orthodontic care.